MASCULINITIES AND ETHNIC CONFLICTS: THE NIGERIAN MILITARY EXPERIENCE, 1966–1970 - Jimoh, Dauda Ishola; Yusuff, Rilwan Olabisi; Yusuf, Muhammad-Bashir Owolabi (Sanata Dharma University, 2025)
This paper examines the masculinities and ethnic tensions within the Nigerian military between 1966 and 1970. The study explores how different ideas of masculinity shaped the way the military operated and how it handled ethnic conflicts. The study sheds light on how various masculinities influenced the emergence of the first military junta, power struggles, and masculine roles during the first military incursion into Nigerian politics and the Nigerian Civil War. The paper relies on primary and secondary sources and adopts both chronological and thematic analyses. This paper contributes to a larger discussion on the intersectionality of masculinity and ethnicity in a military context by recognizing that both ideas contributed to recurring coups and political instability in Nigeria.